Interkoneksi Konsep Walimah Perkawinan dalam Hukum Islam dan Hukum Adat Bugis Bone - Hamzah Latief (Al-Bayyinah, 2019)
AbstractThis study emphasized the interconnection between the concepts of Islamic law and customary law in the marriage ceremony. The focus of this study examined the concept of marriage in Islamic law and customary law, as well as the interconnection between Islamic law and the custom of marriage in Bugis Bone. This study was a descriptive analytical which described the sources obtained and then analyzed. The researcher applied normative and historical social approaches. Comparative methods were used to analyze various data and then correlated one another. This was conducted to measure the interconnection of Islamic law and customary law, therefore the relevant and irrelevant elements can be identified. The results of this study proved that the concept in the implementation of the marriage ceremony showed correlation between Islamic law and customary law of Bugis Bone. Both are considered not contradictory, even the procession of the marriage in Bugis Bone tradition has philosophical values that are in line with the principles of Islamic law. Keywords: Marriage ceremony-Islamic Law-Customary Law.